PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP PERILAKU KONSUMEN DALAM MENGAMBIL KEPUTUSAN PEMBELIAN BUKU DI SENTRAL BUKU KAMPUNG ILMU SURABAYA - SYAIFUL AKBAR, ARIA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Science is one that must be met in people’s live, that one way is to read a book. For the middle to lower consumers would prefer to choose a traditional bookstore that offers books at a cheaper price book although with relatively low quality products. Kampung Ilmu Surabaya whose name is attached to the center of the book sale cheap, also attached to the center of the old book. Variables that researched are product quality (X1), price (X2) and purchase decision (Y) of book at book central Kampung Ilmu Surabaya. This research uses question form and 384 samples by using multiple linear regression. Product quality and price of book at book central Kampung Ilmu Surabaya obtained Fcount of 739,206 and t count of 12,374 for product quality 19,301 for price with a significance level of less than 0,05 we conclude the influence simultaneously and partially between Product Quality and Price for Purchase Decision of book at book central Kampung Ilmu Surabaya, and Price is the most dominant variable influencing Purchase Decision of book at book centrl Kampung Ilmu Surabaya. Keywords : Product Quality, Price, Purchase Decision